Perspective Commentary: The Implementation of Welfare Policies Are Not Held to the Same Ethical Standards as Research: Raising Intergenerational Health Inequality Concerns - Wickham, Sophie; Fancourt, Daisy (Frontiers in Public Health, 2021)
Over the last 12 years the United Kingdom (UK) has seen the introduction of an austerity programme—a fiscal policy—with the primary goal to reduce the government's budget deficit and the role of the welfare system. Between 2010 and 2015 there was an estimated reduction of £14.5 billion in spending, attributable to decreasing the value of benefits and restricting entitlement to benefit claimants. By 2020, there had been an estimated unprecedented £27 billion less spent on welfare compared with spending in 2010. Whilst fiscally-successful at reducing spending, some implemented welfare policies have had direct consequences for people's health, increasing inequalities which have been heavily criticized. Moreover, there is growing concern that this has an intergenerational effect. In this paper, we describe the ethical principles in human research, how these have been considered in public health policy, and the existing evidence of the direct and intergenerational health and welfare consequences of some recent, nationally-implemented welfare policies. We argue that ethical principles, specifically the ethical principle of safety that is applied in all research, should be applied to all public welfare policies to stop the rising inequalities in health we are seeing across generations. We highlight that initial changes implemented to welfare policies as a response to COVID-19 demonstrate that there can be a political and societal perceived value in going further to support individuals and their families during times of adversity, and consider the ethical implications of this.